Wineries and the liability of outsidership: cases from Brazil and Chile - Nogueira, Carlos Eduardo Corrêa; Lorenzi Cancellier, Éverton Luís Pellizzaro de; Alperstedt, Graziela Dias (Revista de Negócios, 2016)
This qualitative research was developed in light of behavioral theories regarding company internationalization. Its objective was to study the internationalization process of two wine exporters, one Chilean and one Brazilian, while focusing on the liability of outsidership.Â Data were collected from primary and secondary sources, mostly from semi-structured interviews with parties responsible for exportation.Â The data was treated with content analysis as grounded in current literature.Â The Undurraga winery (Chile) overcame the liability of outsidership by employing a market penetration strategy consisting of stages, with progression to each consecutive stage depending upon success in the current one.Â When the company enters into a new market, it identifies the liability and develops a strategy to deal with it.Â Even though the Brazilian winery, Salton, is over a century old, it has only attempted to internationalize recently.Â It showed characteristics of liabilities of foreignness and outsidership in practically every period analyzed, and has yet to resolve these problems.